2020
DOI: 10.1128/jvi.00110-20
|View full text |Cite
|
Sign up to set email alerts
|

The Human Cytomegalovirus Transmembrane Protein pUL50 Induces Loss of VCP/p97 and Is Regulated by a Small Isoform of pUL50

Abstract: The human cytomegalovirus (HCMV) UL50 gene encodes a transmembrane protein, pUL50, which acts as a core component of the nuclear egress complex (NEC) for nucleocapsids. Recently, pUL50 has been shown to have NEC-independent activities: downregulation of IRE1 to repress the unfolded protein response and degradation of UBE1L to inhibit the protein ISG15 modification pathway. Here, we demonstrate that a 26-kDa N-terminal truncated isoform of pUL50 (UL50-p26) is expressed from an internal methionine at amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Consistent with multiple roles for VCP during HCMV infections, a recent study has implicated p97 in trafficking of capsids from the nucleus to the cytosol [103] (Figure 3).…”
Section: Viral Genome Replication and P97supporting
confidence: 62%
“…Consistent with multiple roles for VCP during HCMV infections, a recent study has implicated p97 in trafficking of capsids from the nucleus to the cytosol [103] (Figure 3).…”
Section: Viral Genome Replication and P97supporting
confidence: 62%
“…The study suggests a refined model of pUL50 functionality, in which the regulation of viral replication, specifically the nuclear egress, seems to allow some compensatory measures to balance alterations in the expression and phosphorylation levels of pUL50. It has not escaped our notice that pUL50 is not only present at low copy numbers in infectious virions [ 53 ], but also comprises additional, NEC-independent activities [ 54 , 55 ]. Thus, more detailed studies on the virion-associated state of pUL50 may help to understand this multifaceted regulatory aspect in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it remains possible that RNF170 is somehow involved in the degradation of IRE1. A recent study has shown that UL50 also interacts with p97/VCP and downregulates p97 protein levels (33). How exactly UL50 downregulates p97 remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…How exactly UL50 downregulates p97 remains unclear. Interestingly, a short isoform of UL50 lacking the N-terminal 198 amino acids counteracts the downregulation of p97 by the full-length UL50 protein (33). This autoregulatory mechanism appears to be important for viral gene expression, probably because p97/VCP affects the splicing of the major immediate-early transcripts and the expression of the major viral transactivator protein, IE2 (34).…”
Section: Discussionmentioning
confidence: 99%